FENOMENA TRANSAKSI BISNIS ONLINE DI ERA 4.0 - Djuharni, Darti; Dewi, Siutama (Widya Mandala Surabaya Catholic University, 2021)
This research aims to find out online business transactions based on the experience of its business people. This study uses a qualitative research type interpretive approach with phenomenology. In this research researchers use several techniques of collecting data trough: Observation, documentation dan interviews. Based on the research results the researchers found some of these things related to the online business as follows: Entrepreneurial motives, entrepreneurial spirit, the importance of innovation in entrepreneurial, dan the importance of building trust dan honesty in entrepreneurship. The researchers contributions in this study are expected to provide information on online business transactions in the 4.0 era based on individual experiences.